Dimethyl methylphosphonate adsorption and decomposition on MoO2 as studied by ambient pressure x-ray photoelectron spectroscopy and DFT calculations. (9th March 2018) - Head, Ashley R; Tsyshevsky, Roman; Trotochaud, Lena; Yu, Yi; Karslıoǧlu, Osman; Eichhorn, Bryan; Kuklja, Maija M; Bluhm, Hendrik
Abstract: Organophosphonates range in their toxicity and are used as pesticides, herbicides, and chemical warfare agents (CWAs). Few laboratories are equipped to handle the most toxic molecules, thus simulants such as dimethyl methylphosphonate (DMMP), are used as a first step in studying adsorption and reactivity on materials. Benchmarked by combined experimental and theoretical studies of simulants, calculations offer an opportunity to understand how molecular interactions with a surface changes upon using a CWA. However, most calculations of DMMP and CWAs on surfaces are limited to adsorption studies on clusters of atoms, which may differ markedly from the behavior on bulk solid-state materials with extended surfaces. We have benchmarked our solid-state periodic calculations of DMMP adsorption and reactivity on MoO2 with ambient pressure x-ray photoelectron spectroscopy studies (APXPS). DMMP is found to interact strongly with a MoO2 film, a model system for the MoO x component in the ASZM-TEDA© gas filtration material. Density functional theory modeling of several adsorption and decomposition mechanisms assist the assignment of APXPS peaks. Our results show that some of the adsorbed DMMP decomposes, with all the products remaining on the surface. The rigorous calculations benchmarked with experiments pave a path to reliable and predictive theoretical studies of CWA interactions with surfaces.